Police Management and Community Policing: A Case Study from Scotland - Moir, James (International Journal of Business and Social Science Research, 2025)
This paper reports on a case study of police management in Scotland and its focus on orientating the service toward community policing and away from a target-driven approach. Contemporary police report and planning documents are analyzed to chart this shift in orientation towards what is referred to as New Public Governance (NPG) This involves a focus on the public good and represents moving beyond the previous target-driven approach of New Public Management (NPM). New Public Governance stresses community involvement and the co-creation of objectives between professionals and the public they serve. The study examines the extent to which the police service in Scotland is, through formal reporting structures, seeking to align with NPG and if there are vestiges of the NMP approach. A discourse analytic methodology is adopted which examines the rhetorical nature of the documents. The focus of the analysis is the extent to which these public-facing documents represent an attempt to convey police acceptance and enthusiasm for NPG, or if they can be considered as attempts to bolster public confidence and police legitimacy. The ambivalent nature of the discourse in the documents is examined in terms of the adoption of both NPG and NPM through references to key aspects of these managerial approaches, including a focus on the setting of policing objectives through community co-creation in the case of the latter, and stress upon outcomes and measurable outcomes about the former.